Progress Report on the Activities of the Independent Evaluation Office. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Since its last report to the IMFC in April 2009, the IEO has completed its evaluation report on IMF Involvement in International Trade Policy Issues; released the issues papers for the evaluations on the IMF's role in the run-up to the present crisis and on IMF research; and also issued the 2009 Annual Report.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Evaluation; IEO Evaluation; Implementation Plan; PP; Trade Policy Evaluation Report